2020
DOI: 10.1136/jclinpath-2020-207023
|View full text |Cite
|
Sign up to set email alerts
|

High burden of acute kidney injury in COVID-19 pandemic: systematic review and meta-analysis

Abstract: AimsHospitalised patients with COVID-19 have a variable incidence of acute kidney injury (AKI) according to studies from different nationalities. The present systematic review and meta-analysis describes the incidence of AKI, need for renal replacement therapy (RRT) and mortality among patients with COVID-19-associated AKI.MethodsWe systematically searched electronic database PubMed, SCOPUS and Web of Science to identify English articles published until 25 May 2020. In case of significant heterogeneity, the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 44 publications
(33 reference statements)
2
26
0
Order By: Relevance
“…[7][8][9][10] Acute kidney injury (AKI), whose incidence ranged from 0.5% to 40% in COVID-19 patients, could increase the risk of poor outcome and length of hospital stay. 6,[11][12][13][14] Consequently, identifying COVID-19 patients with high risk of developing AKI during hospitalization and therefore making suitable treatment strategies are essential to improve prognosis of patients.…”
mentioning
confidence: 99%
“…[7][8][9][10] Acute kidney injury (AKI), whose incidence ranged from 0.5% to 40% in COVID-19 patients, could increase the risk of poor outcome and length of hospital stay. 6,[11][12][13][14] Consequently, identifying COVID-19 patients with high risk of developing AKI during hospitalization and therefore making suitable treatment strategies are essential to improve prognosis of patients.…”
mentioning
confidence: 99%
“…Endothelial dysfunction, excessive inflammation, ischemic injury and hypercoagulability are considered to be essential mechanisms in the development of acute kidney injury (AKI) in COVID-19. AKI is associated with a 13-fold greater risk of death among SARS-CoV-2 infected individuals [14]. Of note, Menon et al [15] recently showed that renal damage in diabetes and COVID-19 might share common backgrounds, by demonstrating that the diabetic kidney disease angiotensin converting enzyme 2 (ACE2)positive proximal tubular epithelial cell module overlaps with the expression patterns observed in SARS-CoV-2 infected cells.…”
Section: The Rationale Behind the Use Of Sglt2i In Covid-19mentioning
confidence: 99%
“…UK Intensive Care audit data showed renal replacement therapy was delivered in 31% of patients on ventilators, and 4% not on ventilators( 61 ). A recent meta-analysis of 15536 hospitalised patients with COVID-19 determined an overall incidence of AKI of 12.3%, 77% of whom were critically ill. Mortality was 67% in patients with AKI, 13 times higher compared with patients without AKI( 62 ) In comparison, data from H1N1 influenza epidemic, showed that out of those who received intensive care, nearly 18% of patients (without pre-existing CKD) developed AKI and up to two thirds of patients who had a complicated course of H1N1 infection had AKI( 63 ). In contrast, data from the SARS pandemic suggests a lower rate of AKI at 7% of patients hospitalised with the infection, although mortality rate was as high as 90% in patients with renal failure( 64 ).…”
Section: Extra-pulmonary Manifestations Of Covid-19mentioning
confidence: 99%